ChemInform Abstract: Double Transfer of Chirality in Organocopper‐Mediated Bis(alkylating) Cycloisomerization of Enediynes. Issue 36 (9th September 2014) - Campolo, Damien; Arif, Tanzeel; Borie, Cyril; Mouysset, Dominique; Vanthuyne, Nicolas; Naubron, Jean‐Valere; Bertrand, Michele P.; Nechab, Malek
Abstract The synthesis of chiral benzofulvenes, triggered by organocopper reagents, is achieved through a highly chemo‐, regio‐, diastereo‐, and enantioselective bis(alkylating) cycloisomerization process.